The Influence of Service Quality, Facilities and Trust on Customer Satisfaction - Jhonny Mangaraja Silalahi; Sugeng Wahyudi (LifeSciFi, 2025)
This study aims to analyze the impact of service quality, facilities and trust on customer satisfaction at PT Opsico. The urgency of conducting the study is the long queues of gas transport vehicles, delays in LPG delivery due to infrastructure constraints, and the less-than-optimal utilization of available facilities. This condition indicates a mismatch between what customers expect and the quality of service by Opsico. This study implies the importance of managing the LPG supply chain efficiently and sustainably to address the challenges of reliable and environmentally friendly public energy services. The research method was carried out through a quantitative approach. Data collection techniques were carried out through surveys with questionnaires. The total respondents in this study were 85 SPBE/SPPBE. Utilizing the intricate dance of Structural Equation Modeling—Partial Least Squares—the analysis unveiled a profound truth: that service quality, the amenities provided, and the sense of trust weave together to shape the tapestry of customer satisfaction. As these elements ascend in excellence, so too does the contentment of those they serve, suggesting a delicate yet powerful correlation between quality, trust, and the fulfillment found therein.